2018
DOI: 10.3889/oamjms.2018.121
|View full text |Cite
|
Sign up to set email alerts
|

Diabetics Retinopathy Knowledge and Awareness Assessment among the Type 2 Diabetics

Abstract: INTRODUCTION:Diabetic retinopathy (DR) is a leading cause of blindness worldwide. In Saudi Arabia and other Arab countries, several studies estimated the prevalence of DR ranging from 30 - 40%.AIM:To assess the DR knowledge and its association with diabetes control among Type 2 diabetic patients.METHODS:A cross-sectional study of patients with Type II diabetes (T2D) who had a routine visit to the endocrine clinic to assess the DR knowledge and its relation to the glycemic control. We used a questionnaire that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 14 publications
5
34
5
Order By: Relevance
“…On the other hand, poor knowledge of retinopathy delays seeking cares and finally greater risk of blindness. Raising awareness for diabetic patients to know about retinopathy would improve early detection of problems and reduces the delay of seeking ophthalmology care [3], [4]. The present study aimed to evaluate knowledge of 382 diabetic patients about retinopathy and the factors associated with insufficient knowledge among them.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, poor knowledge of retinopathy delays seeking cares and finally greater risk of blindness. Raising awareness for diabetic patients to know about retinopathy would improve early detection of problems and reduces the delay of seeking ophthalmology care [3], [4]. The present study aimed to evaluate knowledge of 382 diabetic patients about retinopathy and the factors associated with insufficient knowledge among them.…”
Section: Discussionmentioning
confidence: 97%
“…Knowledge of retinopathy is an essential step for an appropriate and timely referral. Delay in seeking care is one of the key factors leading to eye complications [3]. Therefore, sufficient knowledge of retinopathy is fundamental to diabetic patients for proper medical care services [4].…”
Section: Discussionmentioning
confidence: 99%
“…Illiterate diabetic patients had seven times higher odds of developing DR than literate patients. Studies conducted in Saudi Arabia [25], Korea [26] and Sudan [18] suggest that less educated or who had no formal education had a high probability of developing DR than who attained higher classes. Another finding from Tokyo suggests that lack of proper educational attainment was significantly associated with the progression of retinopathy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty five percent of the diabetic participants were aware of diabetic retinopathy. However Alzahrani et al, 15 Almalki et al, 16 Lingam et al, 17 and Lian et al 18 reported high prevalence of awareness of diabetic retinopathy among diabetic people. Shah et al reported that 63% of diabetics screened in their study were not aware of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%